Exploring Code – Switching Patterns in Junior High School Students’ English Languange at MTs Amin Darussalam - Ramadhani, Nurul; Arfanti, Yulia (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the patterns and functions of code-switching in English learning at MTs Amin Darussalam, Deli Serdang, North Sumatra. Using a qualitative phenomenological approach, data were collected through classroom observations, audio recordings, and interviews with eighth-grade students during the 2025/2026 academic year. The analysis followed Miles and Huberman’s framework, focusing on data reduction, display, and conclusion drawing. Findings reveal three main types of code-switching: inter-sentential, intra-sentential, and tag switching, with inter-sentential switching being the most frequent. Teachers primarily used code-switching to explain lessons, clarify meanings, and manage classroom interaction, while students employed it to overcome vocabulary limitations and enhance self-expression. Tag-switching served to seek confirmation and maintain classroom rapport. Overall, code-switching was found to facilitate comprehension, build confidence, and create a supportive learning environment. The study concludes that code-switching is a natural and effective communicative strategy in bilingual classrooms.